Intervention study of a foot‐care programme enhancing knowledge and practice among nurses and care workers at in‐home service providers - Kashiko Fujii; Minna Stolt (Wiley, 2020)
Abstract Aim To evaluate the foot‐care educational programme for nurses and care workers at in‐home service providers. Design A non‐randomized controlled study with random cluster sampling method. Methods Study participants were nurses and care workers of 21 in‐home service providers, including home‐visit nursing and care providers, 1‐day care service centres or care centres with rehabilitation programme in Japan. Foot‐care programme with foot‐care tools as a package or standard care comprising 3-5 sessions over 2 months was provided to 110 participants (87 were on analysis). The outcomes were changes in foot‐care knowledge and scores in pre-post interventions. Data were analysed with descriptive statistics, t test, logistic regression analysis and ANCOVA. Results Before adjusting for background, total scores of knowledge and practice categories were higher than the baseline in the intervention group (43 participants) compared with the control group (44 participants). After background correction due to potential bias of non‐random cluster sampling, significant between group differences were observed in mean score changes in skin and consultation subscales of the practice category.